THE USE OF BLOG TECHNOLOGY TO DEVELOP SOCIOCULTURAL SKILLS OF UNIVERSITY STUDENTS AT THE GERMAN LESSONS - Onoshko , Viacheslav; Kryukova , Natalya; Murashkina, Elvira (Revista Inclusiones, 2020)
In recent decades, modern Internet technologies have been actively used in the educational process of universities, namely in the formation of foreign language communicative competence. This study is aimed at presenting scientifically based methodology for the development of sociocultural competence of students of Vyatka State University in the field of Linguistics, with major in Translation and translation theory, based on the use of modern second-generation Internet technology – blog technology, as the intercultural communication effectiveness depends on it. The methods of modeling of the educational process for developing sociocultural skills using blog technology, as well as of experimental training, were the main ones that were used in this work. The applied methods allowed proving the authors’ hypothesis about the effectiveness of using blog technology in accordance with the established authors’ methodology for the development of sociocultural skills.